N450 and LPC Event-Related Potential Correlates of an Emotional Stroop Task with Words Differing in Valence and Emotional Origin - Imbir, Kamil K.; Spustek, Tomasz; Duda, Joanna; Bernatowicz, Gabriela; Żygierewicz, Jarosław (Frontiers in Psychology, 2017)
Affective meaning of verbal stimuli was found to influence cognitive control as expressed in the Emotional Stroop Task (EST). Behavioral studies have shown that factors such as valence, arousal and emotional origin of reaction to stimuli associated with words can lead to lengthening of reaction latencies in EST. Moreover, electrophysiological studies have revealed that affective meaning altered amplitude of some components of evoked potentials recorded during EST, and that this alteration correlated with the performance in EST. The emotional origin was defined as processing based on automatic vs reflective mechanisms, that underlines formation of emotional reactions to words. The aim of the current study was to investigate, within the framework of EST, correlates of processing of words differing in valence and origin levels, but matched in arousal, concreteness, frequency of appearance and length. We found no behavioral differences in response latencies. When controlling for origin, we found no effects of valence. We found the effect of origin on ERP in two time windows: 290-570 ms and 570-800 ms. The earlier effect can be attributed to cognitive control while the latter is rather the manifestation of explicit processing of words. In each case, reflective originated stimuli evoked more positive amplitudes compared to automatic originated words.